Use of Intraprocedural Ibutilide During Stepwise Ablation of Long-Standing Persistent Atrial Fibrillation - Enriquez, Andres (J Atr Fibrillation, 2018)
PURPOSE: Catheter ablation is an effective therapy for symptomatic atrial fibrillation (AF). The aim of this study was to assess the effect of ibutilide administration in patients with long standing persistent AF undergoing catheter ablation. METHODS: We included 25 patients undergoing stepwise catheter ablation with ibutilide 1.0 mg infused prior to mapping and ablation as first step. Procedural and long-term outcomes were compared to a matched cohort of 25 patients in which ibutilide was not used but all other steps remained the same. RESULTS: Mean age of the cohort was 65.6±8.2 years, and duration of persistent AF 71.7±96.8 months. Termination to sinus rhythm (SR) directly or through an atrial tachycardia (AT) was achieved in 88% of patients administered ibutilide (32% SR/68% AT) vs. 64% in the control group. Ibutilide was associated with increased AF mean cycle-length (mCL) (208.3±31.6 vs. 156.0±23.7 ms; p<0.001) and decreased CFE mean surface area (29.2±20.2% vs. 47.3±13.7%; p=0.002). Procedure and radiofrequency (RF) times were less in the ibutilide group (288.8±49.6 vs. 335.3±47.4 min and 66.0±16.0 vs. 78.0±18.2 min; p=0.002 and 0.029 respectively). The 1-year recurrence was 44% in the ibutilide group and 60% in the control groups (p=0.29). Ibutilide patients had significantly reduced ShEn (6.1±0.14 vs. 7.09±0.14; p<0.001) and ShEn was higher in patients that recurred (6.47±0.24 vs. 5.73±0.15; p<0.001). CONCLUSION: In long-standing persistent AF the use of ibutilide in the context of a stepwise ablation results in increased AF mCL, reduction of fractionation and ShEn and higher rates of AF termination, more often through an intermediate AT. Procedure and RF times are also decreased, without compromising long-term outcomes.